Pengaruh Ruang Terbuka Hijau Terhadap Psikologis Masyarakat di Kota Bekasi Khususnya Kecamatan Jatiasih - Eva Kenny Tambunan; Uras Siahaan; M. Maria Sudawarni (Universitas Sebelas Maret Surakarta, 2021)
In the 21st century, mental health disorders such as depression is the most important challenges in urban area. Many residents in urban areas are more at risk of developing depression due to various factors such as lifestyle and unfavorable urban conditions, so we need a space that able to prevent and reduce mental health disorders for urban residents. The aims of this study to examine how the effect of the availability of green open spaces in helping to reduce the level of depression in urban areas. Research methodology that used in this study is descriptive qualitative method, that collects primary by online survey via google docs regarding the Geriatric Depression Scale (GDS), and then continued with an online survey in “The Effect of Green Open Space for Society’s Psychology Communities in Urban”, as well as conducting a survey of several open space in Jatiasih District, and conducting a review of existing literature studies. The result of the analysis that has been carried out, that Green Open Space has influence on psychology, especially to help reduce depression in urban areas.